1996
DOI: 10.1016/s0022-5347(01)66153-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Diagnosis of Bladder Outlet Obstruction in Patients with Benign Prostatic Enlargement and Lower Urinary Tract Symptoms: Development and Urodynamic Validation of a Clinical Prostate Score for the Objective Diagnosis of Bladder Outlet Obstruction

Abstract: T h e J ourn al o f U r o lo g y Copyright © 1996 by A m e r ic a n U ro lo g ic a l A s s o c ia t io n , I n c . Vol. 155, 1649-1654, May 1996 Conclusions: Clinical prostate score shows a superior correlation with bladder outlet obstruc tion than isolated objective parameters or symptom scores. CLINICAL DIAGNOSIS OF BLADDER OUTLET OBSTRUCTION IN PATIENTS WITH BENIGN PROSTATIC ENLARGEMENT AND LOWER URINARY TRACT SYMPTOMS: DEVELOPMENT AND URODYNAMIC VALIDATION OF A CLINICAL PROSTATE SCORE FOR THE OBJECTIVE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0
2

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 15 publications
(7 reference statements)
2
52
0
2
Order By: Relevance
“…During the course of the treatment: the discrepancy between the early onset of maximum symptom score reduction at three months (754%) and the delayed onset of maximum HRQL improvement at twelve months ( 45%) emphasizes the need to measure longterm outcomes according to the patient's perspectives. In the same way, symptom reduction and HRQL improvement were sustained up to 36 months (748% and 43%, respectively); interestingly the storage score was signi®-cantly more reduced than voiding score, and it had been shown that the former was perceived by the patients as the most bothersome 12 and correlated more with HRQL changes. 38 Physical/functional dimension improved more than social life status and mental dimensions, which contrasts with ®ndings of Fowler and coworkers 39 and of Doll and colleagues 40 in patients who underwent surgery (prostatectomy and transurethral resection of prostate, respectively).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…During the course of the treatment: the discrepancy between the early onset of maximum symptom score reduction at three months (754%) and the delayed onset of maximum HRQL improvement at twelve months ( 45%) emphasizes the need to measure longterm outcomes according to the patient's perspectives. In the same way, symptom reduction and HRQL improvement were sustained up to 36 months (748% and 43%, respectively); interestingly the storage score was signi®-cantly more reduced than voiding score, and it had been shown that the former was perceived by the patients as the most bothersome 12 and correlated more with HRQL changes. 38 Physical/functional dimension improved more than social life status and mental dimensions, which contrasts with ®ndings of Fowler and coworkers 39 and of Doll and colleagues 40 in patients who underwent surgery (prostatectomy and transurethral resection of prostate, respectively).…”
Section: Discussionmentioning
confidence: 61%
“…11 Patient's preferences have been proven to be the major in¯uence in the therapeutic choice in BPH and may be different from those of urologists. As mentioned by Rosier and coworkers, 12 the urologist's priorities were based on the degree of obstruction (peak-¯ow, residual urine measurement, pressure-¯ow studies) while patients are mostly bothered by storage symptoms and especially urgency, nocturia and daytime frequency. 13 It is stated that the degree to which urinary dif®culties bother the BPH patient and affects his daily activities varies considerably among individual patients reporting the same symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical prostate score (CLIPS), introduced by Rosier et al, 1 was composed of scores for prostate volume, maximal urinary flow rate, postvoid residual urinary volume, and voided volume and had a superior correlation with urodynamically objective BOO than did isolated parameters. The BOO number (BOON) introduced by van Venrooij and Boon, 2 was calculated from the prostate volume, maximal urinary free flow rate, and relative postvoid residual urine volume, defined as the postvoid residual urine volume divided by the bladder volume at a strong desire to void (times 100%).…”
mentioning
confidence: 99%